EffectiveWatermarking of Digital Audio and Image using Matlab Technique - Subbarayan, Sadasivam; Ramanathan, S.Karthick (IEEE, 2009)
Watermarking is a technique which allows an individual to add hidden copyright notices or other verification messages to digital audio, video, or image signals and documents. In our proposal, for Audio Watermarking, a Watermark is encrypted using RSA Algorithm and is embedded on the audio file using LSB technique. LSB technique is an old technique which is not very robust against attacks. Here, in audio watermarking we have embedded the encrypted watermark on the audio file, due to which removal of the watermark becomes least probable. This would give the technique a very high robustness. In the retrieval, the embedded watermark is retrieved and then decrypted. This method combines the robustness of Transform domain and simplicity of spatial domain methods. For image Watermarking, DWT technique is used. DWT technique is used in Image watermarking. Here, we have embedded the watermark in the image as a pseudo-noise sequence. This gives a remarkable security to the image file as only if the exact watermark is known can the embedded watermark be removed from the watermarked image.